Design and development of power-operated continuous-run potting machine for seedling-nursery - SELVAN, M MUTHAMIL; THANKAMANI, C K; ANNAMALAI, S J K; JAYASHREE, E (The Indian Journal of Agricultural Sciences, 2015)
Potting is still a manual operation in plantation, forestry, and 11 other horticultural nurseries in India and the preparation of pot-mixture and filling in polybags are crucial tasks and are time consuming. Therefore, a poweroperated continuous-run machine was specially designed, fabricated, and tested to master seedling-nursery management capable of mixing, pulverizing, sieving, and filling of pot ingredients in polybags. The machine is a vertical freestanding unit mounted on four legs and consists of 3-hp motor, feed-hopper, pulverizing chamber with 8-numbers of paddles, sieving compartment operated by a slider-crank mechanism, vending instrumentation, and outlet. Ingredients like soil, sand, granite power, farmyard manure, and compost are fed from the top and the pot-mixture is collected at the bottom. Electronic vending is the novelty of the machine, which permits filling pot-mixture at set quantity at set time-gap. Aggregate analysis, degree of pulverization, and other physical parameters of machine-made mixture are at recommended level as well as on par with manually-made pot-mixture. More proportion (81.8%) of desirable level of aggregate was achieved with machine compared in manual method (79.5%) resulted in improved quality of the mixture for seedling establishment. Bagging through machine worked out 71.4% cost-saving and 80.2% time-saving. The machine is recommended for nursery-holders around the nation since the machine can provide pot-mixture for development of saplings of 30 000 numbers per month in a commercial nursery.